Participatory Civic Skill Enforcement through Classroom Community Partnership Learning - Umami, Nadila Nisa Al; Rejekiningsih, Triana; Nuryadi, Muhammad Hendri (International Journal Labs, 2023)
Improvement of the process of growth and development needs to be followed by efforts. Researchers highlight the process of growth and development of adolescents. This study aims to posit the strengthening of students' participatory civic skills in the use of the classroom community partnership learning model which results in active interaction between students in implementing good and intelligent citizenship attitudes. This research was conducted using the research and development research method with the results 1) The application of the classroom community partnership learning model was effectively used in strengthening the civic participation attitude of students to have a sense of ownership between class groups and improving the character of students. 2) students have a sense of openness and concern for each other through good attitudes in community groups in the classroom.